Four new species of the genus Trachelas L. Koch, 1872 and the first record of T. vulcani Simon, 1896 from South-West China (Araneae: Trachelidae) - Jin, Chi; Yin, Xiangchu; Zhang, Feng (Zootaxa, 2017)
Trachelas vulcani Simon, 1896 is recorded from China for the first time. The type species, T. minor O. Pickard-Cambridge, 1872, is redescribed based on specimens from Macedonia. Additionally, four new species of the spider genus Trachelas are described and illustrated: Trachelas brachialis sp. n. (♂, ♀), T. gigapophysis sp. n. (♂), T. gaoligongensis sp. n. (♀) and T. shilinensis sp. n. (♀).